2016
DOI: 10.1155/2016/4320720
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Intervention Program for Parents of Substance-Abusing Youth and Adolescents

Abstract: The use of drugs among adolescents/youth often results in a high degree of distress for the family members who live with them. This in turn can lead to a deterioration of mental (psychological) health, hindering any attempt to successfully cope with the situation. The goal of our research was to study the effect of the Community Reinforcement and Family Training (CRAFT) program on parents of adolescents/young adult drug users. Study volunteers (n = 50) were parents from Valencia (Spain) that were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
2
11
0
1
Order By: Relevance
“…The results of the graphical analysis, the reliable change index, and improvement percentage showed that family-based treatment reduced the craving for substance use by female adolescents. These findings are in line with the results of previous studies (9,14). Biestto Pons et al (14) showed that the family-based intervention program caused a significant improvement in self-esteem, depression, and anger state and decreased negative moods of adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the graphical analysis, the reliable change index, and improvement percentage showed that family-based treatment reduced the craving for substance use by female adolescents. These findings are in line with the results of previous studies (9,14). Biestto Pons et al (14) showed that the family-based intervention program caused a significant improvement in self-esteem, depression, and anger state and decreased negative moods of adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, such participation is predictive of sustainable and satisfactory outcomes (9). According to recent research findings, family-based interventions have a significant effect on improving attitudes toward drugs in students with addicted parents (13), reducing depression and anger in the addicted adolescent (14), increasing self-efficacy and self-esteem, decreasing recurrence rate (15), and prevention of adolescent addiction and failure (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing support to families can have a positive impact on engagement in care, even if the loved one is initially not ready for treatment. [5][6][7][8][9][10][11][12][13][14] The Community Reinforcement and Family Training (CRAFT) model teaches family members to engage loved ones who are not yet ready for behavior change and, importantly, does not rely on the involvement of the individual using alcohol or other drugs. The intervention has three goals: (1) help a loved one move toward treatment, (2) reduce substance use if treatment is not an option, and (3) improve the wellbeing of the engaged family members.…”
Section: Evidencementioning
confidence: 99%
“…En un estudio con 68 pacientes, Hearon et al (2011) encontraron que las mujeres con niveles elevados de ansiedad son más propensas a consumir sedantes que los hombres con los mismos niveles. Por otra parte, si se analiza la ansiedad en relación con el tratamiento de deshabituación, algunos autores observan cómo los niveles de ansiedad son mayores antes de comenzar el tratamiento para la deshabituación de sustancias que cuando este ha finalizado (Marqueta, Jiménez-Muro, Beamonte, Gargallo, & Nerín, 2010); el mismo efecto se produce en la familia (Bisetto, González, & Botella, 2016).…”
unclassified